2018
DOI: 10.7554/elife.37382
|View full text |Cite
|
Sign up to set email alerts
|

Induction of human somatostatin and parvalbumin neurons by expressing a single transcription factor LIM homeobox 6

Abstract: Human GABAergic interneurons (GIN) are implicated in normal brain function and in numerous mental disorders. However, the generation of functional human GIN subtypes from human pluripotent stem cells (hPSCs) has not been established. By expressing LHX6, a transcriptional factor that is critical for GIN development, we induced hPSCs to form GINs, including somatostatin (SST, 29%) and parvalbumin (PV, 21%) neurons. Our RNAseq results also confirmed the alteration of GIN identity with the overexpression of LHX6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 36 publications
1
48
0
1
Order By: Relevance
“…In our current study, LHX6 knockout cell line showed a decreased GIs differentiation efficiency (decreased GABA and GAD67 percentage), while in rodent studies that the GABA neuron number is similar in lhx6 KO mice (Liodis et al, 2007). The percentage of COUPTFII positive cells increased in the LHX6 KO cell line, whereas decreased in the LHX6 overexpression cell lines in our previous observation (Yuan et al, 2018). Correspondingly, lhx6 ko mice studies also showed Lhx6 could repress CGE-identity in MGE cells (Vogt et al, 2014).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…In our current study, LHX6 knockout cell line showed a decreased GIs differentiation efficiency (decreased GABA and GAD67 percentage), while in rodent studies that the GABA neuron number is similar in lhx6 KO mice (Liodis et al, 2007). The percentage of COUPTFII positive cells increased in the LHX6 KO cell line, whereas decreased in the LHX6 overexpression cell lines in our previous observation (Yuan et al, 2018). Correspondingly, lhx6 ko mice studies also showed Lhx6 could repress CGE-identity in MGE cells (Vogt et al, 2014).…”
supporting
confidence: 72%
“…Since LHX6 KO suppressed GIs migration, we determined to further explore if LHX6 overexpression (OE) could promote GIs migration. LHX6 conditional overexpression human pluripotent stem cell (hPSCs) lines was constructed as our previous report (Yuan et al, 2018). GIs were robustly differentiated in both LHX6 OE and control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, the emergence of functional GABAergic inhibition via GABAA receptors is facilitated by a hyperpolarizing shift in the chloride reversal potential during development mediated through activity-dependent increase in the ratio of KCC2:NKCC1 chloride co-transporter expression in neurons 68 . Multiple studies have evaluated the generation of iGABA neurons based on the expression of GABAergic markers and synaptic GABA release [33][34][35][36][37][38]40 . However, to our knowledge it has not been shown before that using direct differentiation of hiPSC into composite E/I networks, iGABAA-FSK develop into neurons that functionally modulate iGLUNgn2 network activity by GABA mediated postsynaptic shunting inhibition and/or hyperpolarizing inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific classes of GABAergic neurons, such as SST + and PV + neurons have been found to have a particularly strong influence on the E/I balance [30][31][32] . Although recent advances in differentiating human induced pluripotent stem cells (hiPSCs) into GABAergic neurons [33][34][35][36][37][38][39][40][41][42] , protocols that enable the generation of SST + and PV + human neurons are still challenging due to the long functional maturation of these cells 43 . Investigating E/I balance in human in vitro models for brain disorders ideally requires a model system that consists of a) neuronal networks In this study, we investigated the role of CDH13 in maintaining E/I balance in a human neuronal model.…”
mentioning
confidence: 99%